Respuesta :

The solution will be x= -10

Simplifying the given expression

[tex]1.8(1.1x - 1.3) - 1.88 = - 24.02[/tex]

Step1: Convert decimal to fraction

[tex]1.8( \frac{11x}{10} - 1.3) - 1.88 = - 24.02[/tex]

[tex]1.8( \frac{11x}{10} - \frac{13}{10} ) - 1.88 = - 24.02[/tex]

[tex]\frac{18}{10} ( \frac{11x}{10} - \frac{13}{10} ) - 1.88 = - 24.02[/tex]

Step2: Make denominator common

[tex]\frac{18}{10} ( \frac{11x - 13}{10}) - 1.88 = - 24.02[/tex]

Step3: Simplifying the fraction

[tex]\frac{9}{5} ( \frac{11x - 13}{10}) - 1.88 = - 24.02[/tex]

Step4: Make denominator common

[tex] \frac{9(11x - 13)}{5 \times 10} - \frac{1.88 \times 50}{50} = - 24.02[/tex]

[tex] \frac{9(11x - 13)}{50} - \frac{94}{50} = - 24.02[/tex]

[tex] \frac{9(11x - 13 - 94)}{50} = - 24.02[/tex]

[tex] \frac{99x - 117 - 94}{50} = - 24.02[/tex]

Step5: Simplifying

[tex] \frac{99x - 211}{50} = - 24.02[/tex]

[tex] 99x - 211 = - 24.02 \times 50[/tex]

[tex] 99x - 211 = - 1201[/tex]

[tex] 99x = - 1201 + 211[/tex]

[tex] 99x = - 990[/tex]

[tex] x = \frac{ - 990}{99} [/tex]

[tex]x = - 10[/tex]

Hence, the solution x=-10

Learn more about simplification here:

https://brainly.in/question/49393260

#SPJ10

ACCESS MORE